Impaired meal stimulated glucagon-like peptide 2 response in ileal resected short bowel patients with intestinal failure. Issue 4 (1st October 1999) - Jeppesen, P B; Hartmann, B; Hansen, B S; Thulesen, J; Holst, J J; Mortensen, P B
Abstract : BACKGROUND: Glucagon-like peptide 2 (GLP-2) is a growth factor for the intestinal epithelium in rodents and may affect intestinal transit. AIMS: To study the GLP-2 response to nutrient ingestion in seven short bowel patients with intestinal failure and seven controls. METHODS: The patients and controls were admitted twice for two test meals after a night of fasting. Meal A was liquid (300 ml, 1.88 MJ); meal B was a regular breakfast (755 g, 3.92 MJ). Plasma samples were collected for 180 minutes; GLP-2 immunoreactivity was measured with an NH2 terminal specific radioimmunoassay. RESULTS: Both meals elicited significant increases in plasma GLP-2 in controls. The magnitude and duration of the responses were dependent on the meal size: the maximum median (25–75%) increases after meal A and B were 24 (3–28) and 48 (33–56) pmol/l. Plasma GLP-2 returned to basal concentrations 180 minutes after meal A, but remained at 50% of peak values after meal B. In the patients neither meal significantly changed the GLP-2 concentration; the maximum median elevation after meal B was 5 (2–8) pmol/l. There were significant differences between patients and controls with respect to the GLP-2 responses to meals A and B. CONCLUSION: Identification of GLP-2 as a tissue specific intestinal growth factor and demonstration of an impaired meal stimulated GLP-2 response in short bowel patients raises the possibility that GLP-2 administration may constitute a new therapeutic strategy, enhancing jejunal adaptation in ileum resected short bowel patients with intestinal failure.